Peran Pemerintah Desa Dalam Meningkatkan Karakter Peduli Lingkungan Pesisir Pada Masyarakat Desa Pulau Kerumputan - Irmasari Irmasari; Wardiani Hiliadi (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This study examines the village government's programs and roles in strengthening environmental care character among coastal communities in Pulau Kerumputan Village, Pulau Laut Kepulauan District, Kotabaru Regency. Using a qualitative case study approach, data were collected through observation, in-depth interviews with seven informants (Village Head, Head of the Village Consultative Body, neighborhood unit head, and community members), and documentation, then analyzed via data reduction, display, and conclusion drawing, with validity ensured through extended observation, triangulation, and member checking. Results show the program is realized through the weekly "Clean Friday" mutual cooperation activity, achieving roughly 60% community participation despite lacking budget support or written policy. Among seven mandated roles under Law No. 6/2014 on Villages, educator, empowerer, and role model roles were effectively carried out through the Village Head's direct example, while policymaker, budget planner, facility provider, and supervisory roles remained weak due to absent formal instruments.